Frequency of QTc interval prolongation in HIV-infected adults from Paraguay in 2020 - González-Cantero, Elen M. (2021)
Introduction: the prolonged QTc interval predisposes to serious arrhythmias. Various medications, including antiretrovirals, can prolong it. The objectives were to determine the demographic, clinical characteristics and the frequency of the prolonged QTc interval in patients with HIV. Methods: we conducted a prospective, observational study with a control group. Men and women, over 18 years of age, with HIV infection, who attended the National Hospital (Itauguá, Paraguay) during 2020, were included. Medical students acted as a control group. All subjects who did not give their consent and those with arrhythmias were excluded. Demographic, clinical, laboratory variables and 12-channel electrocardiogram at rest were measured. The study was approved by the Ethics Committee of the Universidad Privada del Este (Paraguay). Results: 39 HIV patients and 39 healthy controls entered the study. The mean age of the cases was 37 ± 11 years, being 59% male. The most frequent comorbidity in the cases was obesity (7.6%). The mean values ​​of urea, creatinine, K, Ca and Mg in the cases were in the normal range. Prolonged QTc was detected in 18% of the cases and in 0% of the controls. The subjects with the electrocardiographic alteration were all on antiretroviral and multiple antibiotic treatment known to be associated with prolonged Qtc. Conclusion: the frequency of prolonged QTc in HIV patients was 18% and in healthy controls it was 0%. Regular monitoring of the electrocardiogram is recommended in HIV patients receiving drugs that prolong the QT interval.